2016
DOI: 10.1038/nbt.3628
|View full text |Cite
|
Sign up to set email alerts
|

CrispRVariants charts the mutation spectrum of genome engineering experiments

Abstract: CRISPR-Cas9 and related technologies can efficiently alter genomic DNA at targeted positions and have far-reaching implications for functional screening and therapeutic gene editing. Understanding and unlocking this potential requires accurate evaluation of editing efficiency. Here, we show that methodological decisions for analyzing sequencing data can significantly affect mutagenesis efficiency estimates and we provide a comprehensive R-based toolkit, CrispRVariants and an accompanying web tool CrispRVariant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
174
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 22 publications
0
174
0
Order By: Relevance
“…mpv17 crispants showed no apparent other phenotype than iridophore loss and did not have a significantly higher mortality than uninjected siblings at 5 dpf. Sanger sequencing from PCR-isolated clones of the sgRNA target region in injected individuals and allele-level analysis with CrispRVariants (Burger et al, 2016; Lindsay et al, 2016) revealed exceedingly high mutagenesis efficiency, with frameshift deletions as most predominant mutation event that is predicted to result in early termination of translation (Supplemental Figure 1). These results corroborate that direct disruption of the mpv17 ORF results in iridophore defects.…”
Section: Resultsmentioning
confidence: 99%
“…mpv17 crispants showed no apparent other phenotype than iridophore loss and did not have a significantly higher mortality than uninjected siblings at 5 dpf. Sanger sequencing from PCR-isolated clones of the sgRNA target region in injected individuals and allele-level analysis with CrispRVariants (Burger et al, 2016; Lindsay et al, 2016) revealed exceedingly high mutagenesis efficiency, with frameshift deletions as most predominant mutation event that is predicted to result in early termination of translation (Supplemental Figure 1). These results corroborate that direct disruption of the mpv17 ORF results in iridophore defects.…”
Section: Resultsmentioning
confidence: 99%
“…In RGB embryos, dsRED2 labels endothelial, hematopoietic, and endocardial progenitors (lmo2) in red [14], EGFP marks all lateral plate mesoderm lineages (drl) including pectoral fins in green [15], and AmCyan reveals the differentiated cardiomyocytes (myl7 ) in blue [16]; consequently, RGB enables in vivo imaging of all cardiovascular and additional LPM lineages over the first 3 days of development. From F0 outcrosses that transmitted mutant tbx5a alleles, we genotyped adult F1 zebrafish for the presence of mutated tbx5a alleles by tail clipping, PCR, sequencing, and CrispRVariants analysis [17]. From the recovered germline alleles, we kept heterozygous strains for the lesions c.21_25del and c.22_31del (hence forward abbreviated as tbx5a Δ5 and tbx5a Δ10 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CrispRVariants is another tool that offers functionality to analyze deep-sequencing data by quantifying mosaicism and allele-specific gene editing, as well as multisequence alignment views 60 .…”
Section: Introductionmentioning
confidence: 99%